Altered expression of long non-coding RNA GAS5 in digestive tumors. Issue 1 (18th January 2019) - Lu, Shounan; Su, Zhilei; Fu, Wen; Cui, Zhankun; Jiang, Xingming; Tai, Sheng
Abstract : Cancer has become one of the most important diseases that affect human health and life. The effects of cancer in the digestive system are particularly prominent. Recently, long non-coding RNA (lncRNA) has attracted the attention of more and more researchers and has become an emerging field of gene research. The lncRNA growth arrest-specific 5 (GAS5) is a novel lncRNA that has attracted the attention of researchers in recent years and plays an important role in the development of tumors, especially in digestive system tumors. GAS5 was first identified in a mouse cDNA library. It was generally considered that it has the role of tumor suppressor genes, but there are still studies that have a certain ability to promote cancer. Furthermore, the 5-bp indel polymorphism (rs145204276) in the GAS5 promoter region also has a carcinogenic effect. The discovery of GAS5 and in-depth study of single nucleotide polymorphism (SNP) mechanism can provide a new way for the prevention and treatment of digestive system tumors.